Modeling the Relationship between E-Service Quality and Customer Satisfaction: An Empirical Study of Al Salam Algeria Bank - Maroua Djouad; Lilia Boukabara; Rania Bennedjai (Journal of Science and Knowledge Horizons, 2025)
The domain of financial technology has witnessed a significant evolution towards digitization, propelled by groundbreaking advancements in information and communications technology. Financial entities have transitioned from conventional operational frameworks to embrace digital innovations extensively. This research delves into the ramifications of electronic service quality on customer satisfaction at Bank El Salam in Algeria. Employing a methodological approach, the study distributed questionnaires to a sample of 60 clients and analyzed the data utilizing SPSS software version 22. The findings reveal that electronic service quality exerts a substantial and statistically significant impact on customer satisfaction, which is predicated upon three pivotal determinants: customer expectations, perceived performance, and the extent of promise fulfillment at Bank El Salam Algeria.